Human adipose tissue-derived mesenchymal stromal cells inhibit CD4+ T cell proliferation and induce regulatory T cells as well as CD127 expression on CD4+CD25+ T cells - Fiori, Agnese; Uhlig, Stefanie; Klüter, Harald; Bieback, Karen (Cells, 2021)
Mesenchymal stromal cells (MSC) exert their immunomodulatory potential on several cell types of the immune system, affecting and influencing the immune response. MSC efficiently inhibit T cell proliferation, reduce the secretion of pro-inflammatory cytokines, limit the differentiation of pro-inflammatory Th subtypes and promote the induction of regulatory T cells (Treg). In this study, we analyzed the immunomodulatory potential of human adipose tissue-derived MSC (ASC), on CD4+ T cells, addressing potential cell-contact dependency in relation to T cell receptor stimulation of whole human peripheral blood mononuclear cells (PBMC). ASC were cultured with not stimulated or anti-CD3/CD28-stimulated PBMC in direct and transwell cocultures; PBMC alone were used as controls. After 7 days, cocultures were harvested and we analyzed: (1) the inhibitory potential of ASC on CD4+ cell proliferation and (2) phenotypic changes in CD4+ cells in respect of Treg marker (CD25, CD127 and FoxP3) expression. We confirmed the inhibitory potential of ASC on CD4+ cell proliferation, which occurs upon PBMC stimulation and is mediated by indoleamine 2,3-dioxygenase. Importantly, ASC reduce both pro- and anti-inflammatory cytokine secretion, without indications on specific Th differentiation. We found that stimulation induces CD25 expression on CD4+ cells and that, despite inhibiting overall CD4+ cell proliferation, ASC can specifically induce the proliferation of CD4+CD25+ cells. We observed that ASC induce Treg (CD4+CD25+CD127−FoxP3+) only in not stimulated cocultures and that ASC increase the ratio of CD4+CD25+CD127+FoxP3− cells at the expense of CD4+CD25+CD127−FoxP3− cells. Our study provides new insights on the interplay between ASC and CD4+ T cells, proposing that ASC-dependent induction of Treg depends on PBMC activation which affects the balance between the different subpopulations of CD4+CD25+ cells expressing CD127 and/or FoxP3.